Dynamics of the endotoxicosis indices in patients, suffering extended purulent peritonitis - А. Ya. Pavliak; О. V. Pyptiuk (Клінічна хірургія, 2018)
Objective. To investigate the endotoxicosis indices dynamics in patients, suffering extended purulent peritonitis (EPP) during the treatment process.